Humanization of the Shark VNAR Single Domain Antibody Using CDR Grafting. Issue 1 (3rd January 2023) - Zhang, Yi‐Fan; Sun, Yaping; Hong, Jessica; Ho, Mitchell
Abstract: The variable domain of the new antigen receptor (VNAR ) of shark single domain antibodies is evolutionarily distant from the variable regions (VH ) of mammalian immunoglobulins, yet it still has complementarity‐determining regions (CDRs) that are involved in antigen recognition, therefore making it possible to humanize by grafting these CDRs to the framework of human VH homologs. Here, we show the VNAR CDR based on an analysis of currently available VNAR ‐antigen structure complexes in the global Protein Data Bank archive of 3D structure data, and describe the detailed protocol to humanize VNAR by CDR grafting, using B6 (an anti‐ Pseudomonas exotoxin VNAR ), the most common type (Type II) of shark VNAR s, as an example. Ongoing efforts will further optimize the protocol for moving shark VNAR s to the clinic for treating cancer and other human diseases. Published 2023. This article is a U.S. Government work and is in the public domain in the USA. Basic Protocol : Humanize shark VNAR sequence by CDR grafting Support Protocol 1 : VNAR structure prediction and comparison Support Protocol 2 : Measure binding kinetics of humanized VNAR using bio‐layer interferometry (BLI)